Pendidikan Kesehatan tentang Post Partum Blues dan Skrining Edinburgh Postnatal Depression Scale (EPDS) - Dewi Ari Sasanti; Andi Ayub Awu Abdullah; Ummul Khotimah; Della (Universitas Ngudi Waluyo, 2025)
Postpartum Blues is a mood disorder often experienced by mothers after giving birth and can develop into postpartum depression if not detected and treated early. Lack of knowledge of mothers and families regarding postpartum mental health is one of the risk factors for this condition. This community service activity aims to increase the knowledge of postpartum mothers, pregnant women, and cadres regarding Postpartum Blues and conduct early screening for postpartum depression using the Edinburgh Postnatal Depression Scale (EPDS). The methods used include health education through interactive counseling, discussions, and filling out the EPDS questionnaire for postpartum mothers, pregnant women, and cadres. The target group of the activity was postpartum mothers, pregnant women, and cadres in the Gunung Samarinda Village. The results of the activity showed an increase in participants' understanding of psychological changes after childbirth, the signs and symptoms of Postpartum Blues, and the importance of family and health worker support. In addition, EPDS screening helps identify mothers at risk of postpartum depression so that appropriate follow-up can be carried out. This activity is expected to be a preventive and promotive effort in maintaining the mental health of postpartum mothers, pregnant women and cadres as well as improving the quality of maternal health services in the community. Abstrak Post Partum Blues merupakan kondisi gangguan suasana perasaan yang sering dialami ibu setelah melahirkan dan dapat berkembang menjadi depresi pascapersalinan apabila tidak terdeteksi dan ditangani sejak dini. Kurangnya pengetahuan ibu dan keluarga mengenai kesehatan mental masa nifas menjadi salah satu faktor risiko terjadinya kondisi tersebut. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan ibu post partum, ibu hamil dan kader mengenai Post Partum Blues serta melakukan skrining dini depresi pascapersalinan menggunakan Edinburgh Postnatal Depression Scale (EPDS). Metode yang digunakan meliputi pendidikan kesehatan melalui penyuluhan interaktif, diskusi, serta pengisian kuesioner EPDS kepada ibu post partum, ibu hamil dan kader. Sasaran kegiatan adalah ibu nifas ibu hamil dan kader yang berada di Kelurahan Gunung Samarinda. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta mengenai perubahan psikologis setelah melahirkan, tanda dan gejala Post Partum Blues, serta pentingnya dukungan keluarga dan tenaga kesehatan. Selain itu, skrining EPDS membantu mengidentifikasi ibu dengan risiko depresi pascapersalinan sehingga dapat dilakukan tindak lanjut yang tepat. Kegiatan ini diharapkan dapat menjadi upaya preventif dan promotif dalam menjaga kesehatan mental ibu post partum , ibu hamil dan kader serta meningkatkan kualitas pelayanan kesehatan maternal di masyarakat.